Doped potassium dihydrogen phosphate single crystals with enhanced second-harmonic generation efficiency: an investigation of phase purity, nonlinear, piezoelectric, optical, and crystalline qualities. (1st February 2023) - Priyadharshini, R S; Saravanan, M
Abstract: We investigated the impact of itaconic acid (ITA) on potassium dihydrogen phosphate (KDP) aimed at concentrations of 1, 3, and 5 mol % on Single Crystal x-ray Diffraction, Fourier Transform Infra-Red, absorption of optical charm, Powder XRD, improved second Harmonic Generation competency, and third order non-Linearity of fully grown solitary crystals formed by slow cooling (Low Temperature Solution Growth). The crystals were crushed into a powder with micron-sized crystals for x-ray diffraction research. The Powder XRD spectrum of different ITA doped KDP concentrations showed fewer peaks with higher intensities than pure KDP crystals. Doping in the KDP crystal matrix accelerate growth in the [200] plane. Despite vibration assignment modes of ITA doped KDP, the FT-IR spectrum shows doping materials in KDP crystalline media. ITA doped KDP showed 90% optical transmission in UV–vis-NIR spectroscopy, whereas pure KDP possessed 60%. The dielectric investigation found that doped KDP crystals had lower dielectric loss and greater dielectric constants than pure counterparts. In pure and doped crystals, piezoelectric effects and second harmonics are premeditated. Using the Z scan approach, we were able to assess the third order nonlinear optical behaviour of pure crystal samples as well as the effects of self-defocusing caused by doping of ITA in KDP. ITA doping contributes to the growth, nucleation, and induction period. Doping concentration initially accelerated growth. Photoluminescence study shows that fully formed crystals have fewer defects. High Resolution XRD study determined crystal quality.